Basic measurements of radiation at station De Aar (2000-06 - 2020-01) - Lucky Ntsangwane; Danie Esterhuyse (PANGAEA, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from De Aar that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).